Prediction of allosteric sites and mediating interactions through bond-to-bond propensities - B. R. C. Amor (Nature Portfolio, 2016)
Allostery is a key molecular mechanism underpinning control and modulation in a variety of cellular processes. Here, the authors present a method that can be used to predict allosteric sites and the mediating interactions that connect them to the active site of the protein.